INDONESIAN EFL STUDENTS’ THESIS CONCLUSIONS: ORGANIZATIONAL PREFERENCES AND PEDAGOGICAL IMPLICATIONS - Avena, Benedicta; Yumarnamto, Mateus (LLT Journal: A Journal on Language and Language Teaching, 2022)
This paper examines thesis conclusions written by the students of an English education program at a private university in East Java Indonesia. The central question guiding this study is “How do the authors of the theses organize their conclusions?” This study is a genre analysis. The data sources were 24 undergraduate thesis conclusions written from 2017 to 2019, consisting of 12 quantitative theses and 12 qualitative ones. The analysis was conducted in the framework of genre analysis by identifying the major moves and steps. Bunton’s (2005) framework for the generic structure of conclusions was used to understand the data. The results indicate that the majority of the conclusions follow the generic structure with its moves and steps as suggested by Bunton. However, different preferences in organizing the thesis conclusions were apparent between the two groups of thesis conclusions. These findings reflect the mastery of the particular academic genre by the students as well as their preferences in organizing moves and steps. Pedagogical implications of the findings are discussed in teaching English as a foreign language (TEFL).